2012
DOI: 10.1002/car.2195
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Fathers' Involvement in Programmes for the Primary Prevention of Child Maltreatment

Abstract: Both mothers and fathers perpetrate child maltreatment, but it is uncertain the extent to which child maltreatment prevention programmes include fathers. The objectives of this systematic review were to determine: (1) how many empirically studied primary prevention programmes for child maltreatment have included fathers; (2) among studies including fathers, what percentage of participants were fathers; and (3) whether programmes were effective in reducing paternal risk factors for child maltreatment. Three onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 43 publications
1
35
0
5
Order By: Relevance
“…However, data for how well parenting training and/or support programs work with fathers is limited at best (Lee et al, 2013; Osborne et al, 2016; Scourfield, 2014;). Smith, Duggan, Bair-Merritt, & Cox (2012) identified only 2 out of 16 interventions that reported father-specific data in a systematic review of programs targeting abuse and neglect risk.…”
Section: Introductionmentioning
confidence: 99%
“…However, data for how well parenting training and/or support programs work with fathers is limited at best (Lee et al, 2013; Osborne et al, 2016; Scourfield, 2014;). Smith, Duggan, Bair-Merritt, & Cox (2012) identified only 2 out of 16 interventions that reported father-specific data in a systematic review of programs targeting abuse and neglect risk.…”
Section: Introductionmentioning
confidence: 99%
“…The study found that out of 4959 participants in 21 studies across several countries, only 20% of the participants were fathers (Fletcher et al, 2011). Furthermore, a systematic review of father participation in child maltreatment prevention programs, all of which involved a parenting education component, found father participation rates to be less than 30% (Smith, Duggan, Bair-Merritt, & Cox, 2012). These studies reviewed father participation without differentiating between races and ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…The systematic review by Smith et al (2012) unearthed 15 studies, but only two of these reported father-specific outcomes. The systematic review by Smith et al (2012) unearthed 15 studies, but only two of these reported father-specific outcomes.…”
Section: Evidence Of Effectivenessmentioning
confidence: 99%